FOLKTALES OF ZHENG HE IN THE MALAY WORLD: TALES AND ANECDOTES - Dar, Ku Boon (Journal of Al-Tamaddun, 2020)
This article unravels the folktales of the Zheng He armada as it voyaged to the Malay World in the 15th century. Among the tales highlighted are those of the queenfish and durian. Folk literature refers to series of traditional knowledge and cultural beliefs as well as taboos that have been passed down through the generations through oral, written, or symbolic forms. By tracing and navigating through Zheng He’s tales using the qualitative analysis approach, the study of the primary and secondary documents associated with Zheng He and his voyage to the Malay World seeks to dispel the notion that they are mere old wives’ tales told within the community to entertain and pass time. Instead, the tales and anecdotes of Zheng He’s voyage are a valuable resource for practical moral teachings that can be garnered from those stories that relate to the daily lives of the Chinese community in the Malay World. The research findings summarise that understanding Zheng He’s folktales is pertinent in the fostering of cultural exchange and the sharing of moral values between China and the Malay World.